Synthesis, characterizations and anti-corrosion screening of sadimine and brosadimine / Nur Anis Atirah Zulkiflee - Zulkiflee, Nur Anis Atirah (2017)
A Schiff base is a compound that consists of carbon-nitrogen double bond with nitrogen connected to an aryl or alkyl group but not hydrogen. The objectives of this study are to synthesize Schiff bases ligands derived from salicylaldehyde and 5-bromosalicylaldehyde with ethylenediamine, to characterize the synthesized ligands and to carry out anti-corrosion screening on the Schiff bases ligands by weight loss method. Sadimine and Brosadimine ligands were synthesized from the condensation of salicyladehyde with ethylenediamine and 5-bromosalicylaldehyde with ethylenediamine, respectively. Both ligands were refluxed for 5 hours and yielded of 91.37 % and 92.81 %, respectively. These ligands were characterized by elemental analysis, Infrared Spectroscopy, UV-Visanalysis, melting point measurement and anti-corrosion screening. IR and UV analysis suggested the presence of C=N chromophore which confirm the compound of a Schiff base. Both ligands were tested and compared for their effectiveness as corrosion inhibitor by using different concentration, 0.001 M, 0.01 M and 0.1 M. The result stated that the ligand with heteroatom (Br) show higher percentage inhibitor efficiency as compared to the unsubtituted ligand. This may due to the increase electron density by the presence of n benzene and heteroatoms thus provide better absorptivity to the inhibitor. Also, Brosadimine has higher inhibitor efficiency due to their high molecular weight compared to Sadimine.